Diseño e implementación de una biojardinera mediante fitodepuración, para el tratamiento y reutilización de aguas grises domiciliarias en la comunidad de yawari - Shiguango Shiguango, Omar José (2016)
This research was conducted in the Community of Yawari, of the parish and Canton of Archidona, in the Province of Napo, in order to design and build an artificial wetland for the treatment and reuse of gray water generated by the sector’s households through the filtering and purification of water. The methodology was applied through the collection of information in situ, implementation and evaluation of the artificial wetland after its construction, by interpreting the physical-chemical water analysis. The artificial wetland was constructed in a house in the community, and its dimensions were: 1.50 m wide, 4.00 m long and 0.70 m deep. The following plants were sown in the artificial wetland: Canna indica, Canna x generalis, Costus scaber, Heliconia latisphata, Heliconia rostrata and Hedychium coronarium being local plants capable of purifying pollutants. The criteria used to evaluate the obtained results was the methodology outlined by the Unified Secondary Legislation Environment Ministry (Texto Unificado de Legislación Secundaria del Ministerio del Ambiente or TULSMA) text; it was determined that the parameters such as oils and fats, hydrogen potential (pH), chlorides (Cl-), Sulfates (SO4), Fluorides (F-) total solids (TS), Total Suspended Solids (TSS) and Total Phosphorus (P) are below the maximum permissible limits, except the Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD 5). It was concluded that after seven weeks of treatment in the artificial wetland, the treated grey water is not suitable for discharge into a body of fresh water.